Unravelling the dermatological potential of the brown seaweed Carpomitra costata - Susano, Patrícia (2021)
The ever-increasing interest in keeping a young appearance and healthy skin has leveraged the skincare industry. This, coupled together with the increased concern regarding the safety of synthetic products, has boosted the demand for new and safer natural ingredients. Accordingly, the aim of this study was to evaluate the dermatological potential of the brown seaweed Carpomitra costata. The antioxidant, anti-enzymatic, antimicrobial, photoprotective and anti-inflammatory properties of five C. costata fractions (F1–F5) were evaluated. The ethyl acetate fraction (F3) demonstrated the most promising results, with the best ability to scavenge 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals (EC50 of 140.1 g/mL) and the capacity to reduce reactive oxygen species (ROS) production promoted by UVA and UVB radiation in 3T3 cells, revealing its antioxidant and photoprotective potential. This fraction also exhibited the highest anti-enzymatic capacity, inhibiting the activities of collagenase, elastase and tyrosinase (IC50 of 7.2, 4.8 and 85.9 g/mL, respectively). Moreover, F3 showed anti-inflammatory potential, reducing TNF- and IL-6 release induced by LPS treatment in RAW 264.7 cells. These bioactivities may be related to the presence of phenolic compounds, such as phlorotannins, as demonstrated by NMR analysis. The results highlight the potential of C. costata as a source of bioactive ingredients for further dermatological applications.